Computational modelling of head-related transfer function - DOBRUCKI, Andrzej B.; PLASKOTA, Przemysław (Archives of Acoustics, 2007)
Measuring the Head-Related Transfer Function (HRTF) is an efficient method that takes into consideration the influence of the human body on the sound spectrum. The data base used in reproduction of the sound source position is built using the measurement results. The base is individual for each person, which makes it impossible to make a versatile base for all listeners. In this paper a numerical model of artificial head is presented. The model allows to determine the value of HRTF without making measurements. The model includes both geometrical and acoustical parameters. A method which is often used to determine the acoustical field parameters is the boundary element method, which was used to calculate the values of HRTF in this work. In the conclusion results of the calculations are presented and the correctness of the previous assumption made while constructing the geometric part of the numerical human head model is discussed.